DaT18 Database: A Prosopographical Approach to the Study of the Social Structures of Religious Dissent in Mid-Eighteenth-Century Transylvania - NEDICI, Radu (Studia Universitatis Babeș-Bolyai Digitalia, 2020)
Drawing on the many records created by the Habsburg state during the confessional troubles in Transylvania from the 1740s to the 1760s, the DaT18 project merges digital instruments and prosopography to arrive at sketching the social pattern of the Orthodox leadership. This article briefly discusses the technical choices involved in building the relational database that my approach centres on, before talking in more detail about the challenges faced when transposing the information in the primary sources into digital format. First, the question of making use of structured vs. unstructured data, as most of the documents I work with already present some form of tabular layout, while the more narrative ones require different strategies to mitigate losses when converting them. Secondly, the difficult process of record linkage, with many of the persons only mentioned by their first name and no surname to help label each individual entered in more than one source. Lastly, the daunting task of estimating economic resources, since there was no reliable standard in an age that saw four different fiscal systems in use and many regional flavours within the same scheme.